The Use of Edmodo for Teaching Reading in a Blended-Learning Classroom - Desy Rizki Lukitasari; Valentina Andantin Febriyana; Earlyn Gloria (Indonesian Journal of English Language Studies (IJELS), 2019)
The process of teaching and learning in the 21st century is complex. Todays students, who are millennials, may consider the traditional face-to-face classroom setting to be boring and not really motivating anymore. Teachers are required to attend to each students needs and are expected to keep up with what is relevant to todays learning. With the advancement of technology, blended-learning is expected to be one of the solutions. It is when technology is integrated with the teaching and learning process. Hence, this paper discusses how an educational network platform, Edmodo, can be used and is helpful for the blended-learning classroom, as well as the advantages teachers and students can get from using it in teaching reading.